Cosmological Parameters from Eigenmode Analysis of Sloan Digital Sky Survey Galaxy Redshifts - Pope, Adrian C.; Matsubara, Takahiko; Szalay, Alexander S.; Blanton, Michael R.; Eisenstein, Daniel J.; Gray, Jim; Jain, Bhuvnesh; Bahcall, Neta A.; Brinkmann, Jon; Budavari, Tamas; Connolly, Andrew J.; Frieman, Joshua A.; et al. (Astrophysics, 2004)
We present estimates of cosmological parameters from the application of the Karhunen-Loeve transform to the analysis of the 3D power spectrum of density fluctuations using Sloan Digital Sky Survey galaxy redshifts. We use Omega_m*h and f_b = Omega_b/Omega_m to describe the shape of the power spectrum, sigma8 for the (linearly extrapolated) normalization, and beta to parametrize linear theory redshift space distortions. On scales k < 0.16 h/Mpc, our maximum likelihood values are Omega_m*h = 0.264 +/-0.043, f_b = 0.286 +/- 0.065, sigma8 = 0.966 +/- 0.048, and beta = 0.45 +/- 0.12. When we take a prior on Omega_b from WMAP, we find Omega_m*h = 0.207 +/- 0.030, which is in excellent agreement with WMAP and 2dF. This indicates that we have reasonably measured the gross shape of the power spectrum but we have difficulty breaking the degeneracy between Omega_m*h and f_b because the baryon oscillations are not resolved in the current spectroscopic survey window function.